2012
DOI: 10.1002/dneu.22006
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐function analysis of endogenous lectin mind‐the‐gap in synaptogenesis

Abstract: Mind-the-Gap (MTG) is required for neuronal induction of Drosophila neuromuscular junction (NMJ) postsynaptic domains, including glutamate receptor (GluR) localization. We have previously hypothesized that MTG is secreted from the presynaptic terminal to reside in the synaptic cleft, where it binds glycans to organize the heavily-glycosylated, extracellular synaptomatrix required for trans-synaptic signaling between neuron and muscle. In this study, we test this hypothesis with MTG structure-function analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 71 publications
(128 reference statements)
1
25
0
Order By: Relevance
“…MTG regulates VVA synaptomatrix labeling (Rushton et al, 2009), suggesting a mechanistic link between the VVA and MTG changes in Mgat1 mutants. The MTG elevation observed in Mgat1 nulls provides a plausible causative mechanism for strengthened functional differentiation (Rohrbough and Broadie, 2010;Rushton et al, 2012). Consistent with our recent glycosylation gene screen findings , Mgat1 nulls exhibit increased synaptic growth and structural overelaboration.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…MTG regulates VVA synaptomatrix labeling (Rushton et al, 2009), suggesting a mechanistic link between the VVA and MTG changes in Mgat1 mutants. The MTG elevation observed in Mgat1 nulls provides a plausible causative mechanism for strengthened functional differentiation (Rohrbough and Broadie, 2010;Rushton et al, 2012). Consistent with our recent glycosylation gene screen findings , Mgat1 nulls exhibit increased synaptic growth and structural overelaboration.…”
Section: Discussionsupporting
confidence: 89%
“…Conversely, the secreted endogenous lectin MTG is highly elevated in Mgat1 null synaptomatrix, probably owing to attempted compensation for complex and hybrid N-glycan losses that serve as MTG binding sites. MTG binds GlcNAc in a calcium-dependent manner and pulls down a number of HRP-epitope proteins by immunoprecipitation (Rushton et al, 2012), although the specific proteins have not been identified. It will be of interest to perform immunoprecipitation on Mgat1 samples to identify changes in HRP bands.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Dlg, Pak, Dock, and Pix are either reduced or severely mislocalized from mtg mutant synapses, suggesting that MTG plays a critical role upstream of these proteins to regulate GluR localization (Rohrbough et al 2007). Interestingly, when mtg mutants are rescued with MTG lacking its carbohydrate-binding domain (CBD), postsynaptic GluR accumulation increases (Rushton et al 2012). Furthermore, elimination of the CBD does not affect the ability of MTG to bind to glycans, supporting an unexpected function of this domain in limiting the PSD.…”
Section: Regulation Of Synaptic Organizationmentioning
confidence: 99%